Industrial training report: INTEC Education College / Nur Farhana Zamri - Zamri, Nur Farhana (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This industrial training report describes the hands-on experience and abilities I acquired while working in the INTEC Education College library and human resources (HR) departments. I applied my academic knowledge to practical HR and administrative activities by organizing staff files, making a maintenance checklist, maintaining inventory for ACCA textbooks and out-of-date storybooks, and writing campus regulations. These exercises improved my communication, problem-solving, and organizing skills—all of which are critical in a work environment. My comprehension of the function of visual communication in HR was also improved by creating recruitment materials and informational signs. To support the operational objectives of INTEC Education College, this report documents the integration of theoretical knowledge with practical activities, reflecting my professional and personal growth.